The Earthquake Disaster Preparedness Instruments to Support Disaster Response Learning in Kindergartens - Chruasita Dewi Prabarini Putri E.S.; Putu Aditya Antara; I Gede Astawan (Universitas Pendidikan Ganesha, 2020)
This study aims to produce a valid and reliable assessment instruments for earthquake disaster preparedness in kindergarten for group B. This type of research is a research development (Research and Development) carried out using a procedural development model. In the instrument validation stage or the design validation, the assessment was carried out by two material experts. The instrument validation in this study was calculated using the Gregory formula. The product trial stage used 30 students, and the results were calculated using the Alpha Cronbach formula. This research results from the content validity test of 1.00, which is included in the very high category, and the validity test of the resulting items is nine useful items. Test the reliability of the instrument obtained results of 0.66, including high criteria. Therefore, it can be concluded that the instrument developed has been tested for its validity and reliability so that it can be used as an accurate learning assessment tool to measure the level of earthquake disaster preparedness in kindergarten in group B.